A student's dictionary of classical and medieval Chinese - Kroll, Paul W. 1948- (Brill, 2017)
"A Student's Dictionary of Classical and Medieval Chinese facilitates reading and translating historical, literary, and religious texts dating from approximately 500 BCE to 1000 CE. As a lexicon meant for practical use, it also includes an abundance of alliterative and echoic binomes as well as accurate identifications of hundreds of plants, animals, and assorted technical terms in various fields. Comprising over 8,000 characters, an index by "radical" and stroke-number, and various appendices, this is the one reference work for both students and advanced scholars."
Keywords: Mittelchinesisch; Klassisches Chinesisch; Altchinesisch; Englisch; Chinese language / Ancient Chinese, 600-1200 / Dictionaries / English; Chinese language / To 600 / Dictionaries / English; English language / Dictionaries / Chinese; Chinese language; Chinese language / Ancient Chinese; English language; To 1200; Dictionaries; Wörterbuch